Complementary Therapy as an Approach in Managing Occupational Stress - Nur Aishah, Nor Hashim; Florianna Lendai, Michael Mulok; Helmi, Sumilan (Faculty of Cognitive Sciences and Human Development, Universiti Malaysia Sarawak (UNIMAS), 2015)
Occupational stress is caused by various reasons, such as, workload and long working hours. This leads to occurrence of trend in using wellness activities to treat physical and psychological illness that is known as complementary therapy, which is Yoga, Aromatherapy, Qi gong, and Islamic Medical Practices (Ruqyah). Therefore, this research offered a perspective on the use of complementary therapies as a tool in improving and maintaining mental health condition of employees located in Penang, Malaysia. Qualitative method was used where 5 complementary therapy practitioners were interviewed to identify the perceptions towards the use of complementary therapy and to identify the type of therapy that can be practiced to reduce stress, as well as, discuss the benefits of complementary therapies. It was found that complementary therapy is very beneficial as it acts as a holistic treatment, natural way of healing and more empowering, as it helps to improve employee’s mental, emotional and physical health.